2021
DOI: 10.3390/ijerph182212176
|View full text |Cite
|
Sign up to set email alerts
|

Routines, Time Dedication and Habit Changes in Spanish Homes during the COVID-19 Lockdown. A Large Cross-Sectional Survey

Abstract: Many countries chose to establish social distancing as lockdowns after the COVID-19 outbreak. Households had to adapt their day-to-day lifestyles to new circumstances, affecting routines and time dedication to tasks. This national study was carried out to find out how the confinement by COVID-19 affected Spanish households on the perceived habit changes during this period, in relation to their socio-demographic characteristics and household composition. An online questionnaire was launched during the COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…On the other hand, it can be experienced as a burden, negatively affecting both our health and the quality of care provided [ 59 ]. This may be due to the combination of emotional and physical fatigue that caring entails, increased by the pandemic situation [ 60 ], lack of resources and space and the suddenly enforced proximity with immediate family [ 39 ], especially if relationships were already strained. The weight of social norms and gender inequalities means that female caregivers, particularly low income or single parents, still experience greater levels of burden [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it can be experienced as a burden, negatively affecting both our health and the quality of care provided [ 59 ]. This may be due to the combination of emotional and physical fatigue that caring entails, increased by the pandemic situation [ 60 ], lack of resources and space and the suddenly enforced proximity with immediate family [ 39 ], especially if relationships were already strained. The weight of social norms and gender inequalities means that female caregivers, particularly low income or single parents, still experience greater levels of burden [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…An online survey study reported that 34.3% of working women experienced a higher physical load owing to household chores during the COVID-19 lockdown [ 25 ]. Another online study demonstrated that women were more dedicated to home care and domestic chores during the COVID-19 lockdown [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some may even regard this as a violation of their basic freedoms, causing disappointment with their governments and paradoxically instigating a sense of insecurity rather than protection ( Cheung and Ip, 2020 ). Above all that, the lifestyles during a lockdown present a radical discontinuity with the usual lifestyles (such as switching to home-office and/or home-schooling arrangements, spending an unusually large amount of time with family members and so on) ( De Haas, Faber and Hamersma, 2020 ; Navas-Martín et al, 2021 ), and adapting to those can be a source of great stress and frustration in itself (e.g., Abd El-Fatah et al, 2021 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%